Persepsi Mahasiswa UINSU Tentang Pentingnya Penerapan Pancasila - Randi, Muhammad Sinar; Salsabila, Nadiah; Syakilah, Aisyah; Khairunnida, Nayla; Lubis, Nurul Yulia Riski (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Pancasila serves as the fundamental principles of values in Indonesian society, nation, and government, playing a central role as the cornerstone of the country. Given the ongoing social, cultural, and political transformations, it is crucial to grasp the perspectives of students at North Sumatra State Islamic University (UINSU) on the importance and pertinence of incorporating Pancasila into their daily lives. The purpose of this study is to evaluate the viewpoints of UINSU students regarding the significance of incorporating Pancasila. The chosen research approach involved conducting a survey with UINSU students from different academic programs, where a questionnaire was distributed to gather information. The data was examined using a qualitative method to gain an understanding of students' perspectives on Pancasila values and how they apply to daily life. The findings of the study indicate that most participants recognize the significance of Pancasila in developing the national character and identity, despite variations in their comprehension and recognition of these principles.